The physico-chemical plant defenses and its effect on ruminant feeding - Camacho-Escobar, Marco Antonio; Ramos-Ramos, Diego Arturo; Ávila-Serrano, Narciso Ysac; Sánchez-Bernal, Edgar Iván; López-Garrido, Serafín Jacobo (REVISTA TERRA LATINOAMERICANA, 2020)
Plants are consumed by various organisms, this situation puts their survival at risk, so they have developed defense mechanisms that prevent their intake. For example, anatomical adaptations, chemical defenses or secondary metabolites. These phytochemicals inhibit the attack of pathogens, cause contact irritation, affect the cutaneous, gastrointestinal, cardiac and nervous systems of herbivores or can cause death. Ruminants have mechanical, physiological and ethological adaptations to evade plant defenses: rejection, regulation and biotransformation. They developed anatomic-physiological adaptations to house microbial symbionts to degrade cellulose and plant toxins. Some secondary metabolites may have beneficial effects in food or animal medicine, but more study needed on the subject.